Wing scale ultrastructure underlying convergent and divergent iridescent colours in mimetic Heliconius butterflies. Issue 141 (18th April 2018) - Parnell, Andrew J.; Bradford, James E.; Curran, Emma V.; Washington, Adam L.; Adams, Gracie; Brien, Melanie N.; Burg, Stephanie L.; Morochz, Carlos; Fairclough, J. Patrick A.; Vukusic, Pete; Martin, Simon J.; Doak, Scott; et al.
Abstract : Iridescence is an optical phenomenon whereby colour changes with the illumination and viewing angle. It can be produced by thin film interference or diffraction. Iridescent optical structures are fairly common in nature, but relatively little is known about their production or evolution. Here we describe the structures responsible for producing blue-green iridescent colour in Heliconius butterflies. Overall the wing scale structures of iridescent and non-iridescent Heliconius species are very similar, both having longitudinal ridges joined by cross-ribs. However, iridescent scales have ridges composed of layered lamellae, which act as multilayer reflectors. Differences in brightness between species can be explained by the extent of overlap of the lamellae and their curvature as well as the density of ridges on the scale. Heliconius are well known for their Müllerian mimicry. We find that iridescent structural colour is not closely matched between co-mimetic species. Differences appear less pronounced in models of Heliconius vision than models of avian vision, suggesting that they are not driven by selection to avoid heterospecific courtship by co-mimics. Ridge profiles appear to evolve relatively slowly, being similar between closely related taxa, while ridge density evolves faster and is similar between distantly related co-mimics.